THE KASHMIRI SHAWL: RETHINKING PERSPECTIVES OF AUTHENTICITY AND APPROPRIATION IN POST-COLONIAL ERA (Proceeding of the International Conference on Arts and Humanities, 2019)
The twentieth century can be characterized by intensive cultural transfer and movement which followed two major modes; that of hybridity and consumption. Hybridity being best typified by the appropriations of non-European culture by the 60s counter-culture movement, while consumption by a vibrant cultural tourism economy along with the objectification and commodification of hypostatized cultural products through the souvenir and exotica industry. These developments have created a rich material-visual culture and inventory of cultural expression which in the post-millennial era has brought the ideas of appropriation and authenticity to the forefront of public and intellectual discourse. This study uses the case of the Kashmiri shawl to critique and analyse current ideas of cultural authenticity and appropriation in view of building a theoretical framework that charts out these cultural processes along three axes; cultural zones (horizontal), historical progression (lateral) and social stratification (vertical). This axial perspective aims to create a conceptual model for mapping cultural landscapes that carries the combined theorizing and analytical potential lacking in current models for understanding cultural transfer: a) a model for theorizing ideas like appropriation clearly through an independent structural model of culture; b) a nuanced model that maps out cultural landscape along three dimensions of cultural movement; c) a global model that consolidates different cultural terrains into one interconnected whole.
Keywords: appropriations; authenticity; hybridity; post-colonialism; culture